2016
DOI: 10.3168/jds.2015-10372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk replacer program on calf performance and digestion of nutrients with age of the dairy calf

Abstract: Calves fed large amounts of milk replacer (MR) gain more body weight preweaning than calves fed less-aggressive programs; however, postweaning growth may be reduced. Limited research suggests that less than optimal digestion of the postweaned diet due to large amounts of MR with reduced dry feed intake preweaning may contribute to growth impairment postweaning. Current research was conducted to compare growth and postweaning digestion in 3-d-old male Holstein calves fed various MR programs. The MR programs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
51
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 37 publications
13
51
2
1
Order By: Relevance
“…Our results support research by Cowles et al (2006), Guindon et al (2015), and Chapman et al (2016), that observed calves consuming up to 0.9 to 1.3 kg DM of MR daily during the preweaning period gained more weight, had greater skeletal growth, and were more efficient than calves fed approximately 0.5 kg DM of MR. As shown in Figure 1, we found a significant treatment by week interaction for starter intake that resulted in an overall treatment effect. Overall, calves on the accelerated feeding programs consumed less starter than conventionally fed calves, which was attributed to the greater difference in starter intake during wk 3, 4, 5, and 6 of the preweaning period.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results support research by Cowles et al (2006), Guindon et al (2015), and Chapman et al (2016), that observed calves consuming up to 0.9 to 1.3 kg DM of MR daily during the preweaning period gained more weight, had greater skeletal growth, and were more efficient than calves fed approximately 0.5 kg DM of MR. As shown in Figure 1, we found a significant treatment by week interaction for starter intake that resulted in an overall treatment effect. Overall, calves on the accelerated feeding programs consumed less starter than conventionally fed calves, which was attributed to the greater difference in starter intake during wk 3, 4, 5, and 6 of the preweaning period.…”
Section: Discussionsupporting
confidence: 91%
“…Digestibility results were opposite those of other trials (Terré et al, 2007a,b;Hill et al, 2010, Chapman et al, 2016. However, those earlier experiments determined nutrient digestibilities after calves were weaned, whereas in the current study, calves were still being fed MR. Hill et al (2010) observed reduced DM and OM digestibility in the immediate 3 d postweaning with calves fed up to 1.1 kg DM of MR daily.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…During the nursery trial, ADG per unit of ME intake or CP intake did not differ. This was previously reported and discussed by Chapman et al (2016). Calves fed HI used nutrients no more efficiently than calves fed MOD throughout the 56-d nursery period (Table 2).…”
Section: Discussionsupporting
confidence: 73%
“…We are aware of 5 estimates of digestibility postweaning in calves fed low versus high amounts of MR. Each reported lower OM digestibility in calves when MR DMI was greater than about 0.7 kg of DMI daily compared with calves fed less than 0.7 kg of DM daily. Terre et al (2007a,b), Hill et al (2016b), and Chapman et al (2016) compared low and moderate (0.4 to 0.7 kg of DMI from MR) and high (0.9 to 1.1 kg DMI from MR) feeding programs and found less OM and fiber digestion postweaning with high versus moderate and low MR feeding programs. Reduced digestibility in calves fed more MR was likely associated with less development of the rumen (Terre et al, 2007a,b;Suarez-Mena et al, 2011) because of lower preweaning starter intake.…”
Section: Introductionmentioning
confidence: 99%